Special issue: Customer empowerment - Geyer-Schulz, AndreasMeyer-Waarden, Lars (Customer & Service Systems / Andreas Geyer-Schulz, Lars Meyer-Waarden (Eds.). Karlsruher Institut für Technologie (KIT), Institut für Informationswirtschaft und Marketing, 2014)
The second French-German workshop about Consumer Empowerment took place at the University of Karlsruhe (KIT) between January 10-11, 2013. Within the scope of consumer empowerment scientists discussed recent developments in this field and established cross-disciplinary coop- erations in their own fields of research.